2019
DOI: 10.1590/0034-7167-2018-0497
|View full text |Cite|
|
Sign up to set email alerts
|

The meaning of a “good nurse” in pediatric care: a concept analysis

Abstract: Objective: to analyze the attributes, antecedents and consequences of the concept a “good nurse” in the context of Pediatrics. Method: concept analysis study based on Rodgers’ evolutionary method. Theoretical stage consisted of searching for articles in the CINAHL, Embase and Pubmed databases and a practical stage of semi-structured interviews with pediatric nurses. The final analysis unified the two stages by categories of antecedents, attributes and consequences of the concept. Results: 20 articles and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…In this study, we observed that communication permeates the quality of relationships. This finding is supported by both clinical and theoretical research (Santos et al, 2019b; Davies et al, 2017; Snaman et al, 2017; Weaver et al, 2016). Reciprocal communication is the basis for establishing caring relationships among nurses, patients, and families.…”
Section: Discussionsupporting
confidence: 65%
“…In this study, we observed that communication permeates the quality of relationships. This finding is supported by both clinical and theoretical research (Santos et al, 2019b; Davies et al, 2017; Snaman et al, 2017; Weaver et al, 2016). Reciprocal communication is the basis for establishing caring relationships among nurses, patients, and families.…”
Section: Discussionsupporting
confidence: 65%
“…[14][15][16][17] Para que se obtenha um bom resultado da equipe de enfermagem, é necessário que esta seja referência em profissionais dotados de qualidades como compaixão, empatia, honestidade, integridade, coragem, moral, confiabilidade, paciência e sabedoria, que uma pessoa possa visualizar e sentir na mesma perspectiva as experiências vivenciadas por outra, que a comunicação seja efetiva permitindo se aliar a compreensão no cuidado com o paciente para o sucesso do atendimento. 18 Pesquisa realizada em duas escolas de enfermagem de uma universidade pública do sudoeste da Espanha, relata que a empatia produz um efeito positivo na melhoria dos resultados de saúde do paciente, tornando-se uma habilidade fundamental em qualquer relacionamento pessoal. Ainda existe uma carência de metodologias mistas na pesquisa de empatia, onde faz-se necessário um treinamento em competência empática para o aprimoramento da aprendizagem e compreensão de habilidades.…”
Section: Discussionunclassified
“…Great interpersonal skills that allow the nurse to show respect for individuality and communicate appropriately are attributes highly upheld by patients across the lifespan (Randall & Hill, 2012;Santos et al, 2019;Riviere et al, 2019;Sanakova & Cap, 2019) and among multi-ethnic patients (Goh et al, 2016). There is empirical evidence depicting a strong relationship between the interpersonal skills of nurses and patient satisfaction (Kim-Soon, Musbah, & Ahmed, 2017;Prip et al, 2017).…”
Section: Attributes Of the Nurse As Prerequisites Of Person-centered ...mentioning
confidence: 99%